Composite anti-seepage paint, preparation method thereof and composite anti-seepage paint coating

By combining fluorescent probe molecules with modified hydroxyapatite and combined with epoxy resin and curing agent, a composite anti-seepage coating was prepared, which solved the problem that existing coatings were difficult to take into account both self-diagnosis, self-repair and anti-corrosion barrier properties, and achieved efficient self-diagnosis and self-repair functions of the coating.

CN119592174AActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311165065.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

Existing anti-seepage coatings are difficult to take into account both self-diagnosis, self-repair function and anti-corrosion barrier properties, resulting in insufficient metal corrosion detection and protection.

Method used

By mixing fluorescent probe molecules with modified hydroxyapatite and combining with epoxy resin and curing agent, a composite anti-seepage coating is prepared, which can produce a fluorescent indicator effect during local damage and inhibit metal corrosion through the stress release mechanism of modified hydroxyapatite.

Benefits of technology

The self-diagnosis function of the coating is realized, which can generate fluorescent signals when metal corrosion occurs, and improve the anti-corrosion and anti-seepage performance of the coating through the self-healing mechanism of modified hydroxyapatite, making up for the shortcomings of the existing technology.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of anti-seepage coatings, and discloses a composite anti-seepage coating, a preparation method thereof and a composite anti-seepage coating coating, and the method comprises the following steps: 1) in the presence of a solvent, mixing fluorescent probe molecules and modified hydroxyapatite, and drying to obtain a solid product containing a fluorescent molecular probe; (2) the solid product in the step (1) is mixed with epoxy resin and a curing agent, the composite anti-seepage coating is obtained, the dosage mass ratio of the fluorescent probe molecules to the modified hydroxyapatite is 1: (5-35), and the modified hydroxyapatite is molecular sieve imidazole framework material grafted hydroxyapatite. The preparation method of the composite anti-seepage coating has the advantages that the self-diagnosis performance, the physical barrier performance and the anti-seepage performance of the coating are more excellent, the defect that an existing coating technology cannot have the self-diagnosis function and the self-repairing function at the same time is overcome, and application and development of the high-anti-seepage anti-corrosion coating are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of anti-seepage coatings, and in particular to a composite anti-seepage coating and a preparation method thereof, and a composite anti-seepage coating coating. Background Art

[0002] Fluorescent probes have been widely used in the field of metal corrosion detection and damage location due to their unique photoluminescence properties. This technology uses the change in fluorescence signals generated by the combination of fluorescent probes and metal ions or H+ / OH- ions generated by corrosion to indicate the occurrence of corrosion. Compared with traditional metal corrosion detection methods such as weightlessness, electrochemical method, noise method, X-ray method and ultrasonic method, fluorescent probe technology can detect the initial corrosion of metals, and has the advantages of in-situ, intuitive, high sensitivity, and completely non-destructive to the detected metal during the detection process. As a new type of metal corrosion detection method, fluorescent probe technology is also widely used in metal anti-corrosion coatings. Adding fluorescent probes to organic resins to mix and form composite coatings can make the prepared coatings have self-detection functions, and applying the coatings to the steel surface to construct intelligent coatings with corrosion self-diagnosis functions. When the coating is damaged, the iron ions or H+ / OH- ions generated by steel corrosion react with the fluorescent probes to generate fluorescent signals, realizing the diagnosis of steel corrosion. However, this technology also has the problem that the fluorescent probes have poor stability and will react with organic resins or additives in the coatings, thereby reducing the barrier and shielding properties of the coatings against corrosive media. Porous nanomaterials have important application prospects in the field of coatings. Their ample internal cavities can serve as excellent carriers of active substances. By further dispersing the porous nanomaterials evenly in the coating, when defects occur in the coating, the nanomaterials can be stimulated to respond to signals and actively release active substances, thereby repairing the coating defects. The use of porous nanomaterial loading technology can prevent the active substances from directly contacting the coating and causing deactivation reactions, thereby affecting the performance of the coating. However, the application conditions of porous nanomaterials in coatings are relatively strict, and their loading capacity and self-healing effect need to be improved through preparation process optimization and regulation.

[0003] CN105802452A discloses a method for preparing a graphene coating, which mainly comprises dispersing graphene in a resin to prepare an anti-corrosion coating with a partial anti-seepage function.

[0004] CN114686085A discloses a corrosion self-diagnostic coating based on ion exchange and a preparation method thereof. The coating is mainly made by mixing copper salt substances, organic ligands and organic resins and applying them to the target metal surface. The anti-corrosion coating prepared by this method will produce obvious color changes after being damaged, thereby realizing the diagnosis of steel corrosion.

[0005] CN114618760A discloses a photothermal response nanofiber self-repairing coating and a preparation method thereof, which is mainly to load the photothermal agent hydroxy copper nitrate nanoparticles on the surface of the nanofiber through self-assembly, add them to an organic resin to make a coating, and apply them on the metal surface to make a coating. When the metal surface is damaged, the coating can stimulate the photothermal effect of the photothermal agent hydroxy copper nitrate nanoparticles loaded on the nanofiber through light, converting light into heat, and realizing rapid repair of the damaged cracks of the organic coating.

[0006] These three solutions only enhance the corrosion resistance, self-diagnosis or self-repairing performance of the coating, but fail to take into account all the performances. Therefore, it is of great significance and necessity to develop an anti-seepage coating that has both self-diagnosis and self-repairing functions and anti-corrosion barrier properties. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems existing in the prior art and to provide a composite anti-seepage coating and a preparation method thereof and a composite anti-seepage coating coating, wherein the composite anti-seepage coating can respond to the stimulation signal of local damage to produce a fluorescent indication effect, and inhibit the corrosion process of exposed metal at the defective position, thereby exhibiting excellent anti-seepage and anti-corrosion properties.

[0008] In order to achieve the above object, the present invention provides a method for preparing a composite anti-seepage coating, which comprises the following steps:

[0009] 1) In the presence of a solvent, mixing the fluorescent probe molecule and the modified hydroxyapatite, and drying them to obtain a solid product containing the fluorescent molecular probe;

[0010] 2) mixing the solid product described in step 1) with an epoxy resin and a curing agent to obtain a composite anti-seepage coating;

[0011] The mass ratio of the fluorescent probe molecule to the modified hydroxyapatite is 1:5-35.

[0012] The modified hydroxyapatite is hydroxyapatite grafted with molecular sieve imidazole framework material.

[0013] Preferably, the mass ratio of the fluorescent probe molecule to the modified hydroxyapatite is 1:15-25.

[0014] Preferably, the weight ratio of the modified hydroxyapatite to the solvent is 1:80-120.

[0015] Preferably, the solvent is one or more of ethanol, ether and phenol, preferably ethanol.

[0016] Preferably, the fluorescent probe molecule is one or more of N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide, N-(2-thiazolyl)-4-(1-piperidinyl)-1,8-naphthalimide and N-(2-pyridinyl)-4-(1-piperidinyl)-1,8-naphthalimide, preferably N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide.

[0017] The mixing conditions include: temperature of 20-30°C, time of 8-12h, and pressure of 8-12MPa;

[0018] Preferably, the mixing conditions include: temperature of 24-26°C, time of 9-11h, and pressure of 10-11MPa;

[0019] Preferably, the drying is centrifugal drying, and the drying conditions include: a centrifugal speed of 4000-8000 rpm, a temperature of 50-70°C, and a time of 2-6h; more preferably, the drying conditions include: a centrifugal speed of 5000-7000 rpm, a temperature of 55-65°C, and a time of 3-5h.

[0020] Preferably, the molecular sieve imidazole framework material is a metal organic framework material, preferably a metal organic framework material ZIF-7.

[0021] Preferably, the modified hydroxyapatite is obtained by contacting hydroxyapatite with benzimidazole and zinc nitrate in the presence of an organic solvent.

[0022] Preferably, the mass ratio of the hydroxyapatite, benzimidazole and zinc nitrate is 1:16-17:5-6.

[0023] Preferably, the mass ratio of the hydroxyapatite to the organic solvent is 1:80-120.

[0024] Preferably, the organic solvent is dimethylformamide.

[0025] Preferably, the mass ratio of the solid product, the epoxy resin and the curing agent is 1:11-16:3-9; more preferably, the mass ratio of the solid product, the epoxy resin and the curing agent is 1:12-15.6:3.6-7.

[0026] Preferably, the epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin.

[0027] Preferably, the curing agent is one or more of diethylenetriamine, triethylenetetramine and hydroxyethylethylenediamine.

[0028] Preferably, the method further comprises, after the mixing, vacuum degassing the mixed product.

[0029] The vacuum degassing conditions include: vacuum pressure of -0.03 to -0.08 MPa and temperature of 25-35°C.

[0030] According to a second aspect of the present invention, there is provided a composite anti-seepage coating prepared by the method for preparing the composite anti-seepage coating according to the first aspect of the present invention.

[0031] According to the third aspect of the present invention, a composite anti-seepage coating is provided, wherein the composite anti-seepage coating is prepared using the composite anti-seepage coating prepared by the preparation method of the composite anti-seepage coating described in the first aspect of the present invention or the composite anti-seepage coating described in the second aspect of the present invention.

[0032] Preferably, the composite anti-seepage coating is obtained by coating the composite anti-seepage coating on the surface of a substrate and then curing the composite anti-seepage coating.

[0033] Through the above technical scheme, the fluorescent probe molecules encapsulated in the molecular sieve imidazole skeleton modified hydroxyapatite nanocontainer in the present invention avoid direct contact with other components of the coating, making the self-diagnosis performance of the coating better. In addition, after the molecular sieve imidazole skeleton modified hydroxyapatite is corroded, the benzimidazole produced by stress release can inhibit the corrosion process of the metal. It has excellent physical barrier properties and excellent anti-seepage properties, which makes up for the shortcomings of the current existing coating technology that cannot have both self-diagnosis and self-repair functions, and is conducive to promoting the application and development of high anti-seepage anti-corrosion coatings. DETAILED DESCRIPTION

[0034] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0035] According to a first aspect of the present invention, a method for preparing a composite anti-seepage coating is provided, wherein the method comprises:

[0036] 1) In the presence of a solvent, mixing the fluorescent probe molecule and the modified hydroxyapatite, and drying them to obtain a solid product containing the fluorescent molecular probe;

[0037] 2) mixing the solid product in step 1) with epoxy resin and curing agent to obtain a composite anti-seepage coating.

[0038] The mass ratio of the fluorescent probe molecule to the modified hydroxyapatite is 1:5-35.

[0039] The modified hydroxyapatite is hydroxyapatite grafted with molecular sieve imidazole framework material.

[0040] In the present invention, the modified hydroxyapatite is a molecular sieve imidazole framework material grafted with hydroxyapatite, and "molecular sieve imidazole framework material grafted with hydroxyapatite" refers to a material on which hydroxyapatite is grafted onto a molecular sieve imidazole framework material.

[0041] The molecular sieve imidazole framework material is preferably a metal organic framework material, and more preferably a metal organic framework material ZIF-7.

[0042] According to the present invention, preferably, the mass ratio of the fluorescent probe molecule to the modified hydroxyapatite is 1:5-35; more preferably, the mass ratio of the fluorescent probe molecule to the modified hydroxyapatite is 1:15-25.

[0043] According to the present invention, preferably, the weight ratio of the modified hydroxyapatite to the solvent is 1:80-120.

[0044] According to the present invention, in order to improve the loading efficiency of the fluorescent molecular probe and the solubility of the reactants, the solvent contained in step 1) is preferably selected from one or more of ethanol, ether and phenol; more preferably, the solvent is ethanol.

[0045] According to the present invention, in order to enable the anti-seepage coating to respond to the corrosion signal of the base metal to produce a fluorescent indication effect and realize the corrosion self-diagnosis function, preferably, the fluorescent probe molecule is one or more of N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthaleneimide, N-(2-thiazolyl)-4-(1-piperidinyl)-1,8-naphthaleneimide and N-(2-pyridinyl)-4-(1-piperidinyl)-1,8-naphthaleneimide; more preferably, the fluorescent probe molecule is N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthaleneimide.

[0046] According to the present invention, preferably, the mixing conditions include: temperature of 20-30°C, time of 8-12h, and pressure of 8-12MPa; more preferably, the mixing conditions include: temperature of 24-26°C, time of 9-11h, and pressure of 10-11MPa.

[0047] According to the present invention, the drying may be carried out by a method commonly used in the art. Preferably, the drying is centrifugal drying.

[0048] Preferably, the drying conditions include: a centrifugal speed of 4000-8000 rpm, a temperature of 50-70°C, and a time of 2-6h; more preferably, the drying conditions include: a centrifugal speed of 5000-7000 rpm, a temperature of 55-65°C, and a time of 3-5h.

[0049] According to the present invention, in step 1), the amount of the solvent can be selected according to the amount of the modified hydroxyapatite. Preferably, in step 1), the weight ratio of the modified hydroxyapatite to the solvent is 1:80-120; more preferably, the weight ratio of the modified hydroxyapatite to the solvent is 1:90-110.

[0050] In the present invention, in order to encapsulate the fluorescent probe molecules, it can effectively prevent the fluorescent probe molecules from combining with the organic resin and additives in the coating and becoming ineffective. When the coating is corroded, it can respond to the pH changes caused by metal corrosion, release benzimidazole to repair the corroded base part, and release the internal fluorescent probe molecules to cause a fluorescent reaction, thereby realizing the corrosion self-diagnosis function. The modified hydroxyapatite is a molecular sieve imidazole skeleton material grafted with hydroxyapatite.

[0051] In the present invention, preferably, the molecular sieve imidazole framework material grafted hydroxyapatite is obtained by contacting hydroxyapatite with benzimidazole and zinc nitrate in the presence of an organic solvent.

[0052] The hydroxyapatite may be a commercially available product or may be synthesized according to a conventional method in the art.

[0053] For example, hydroxyapatite can be obtained by the following method.

[0054] NH4H2PO4 and Ca(NO3)2 are dissolved in deionized water and then ultrasonically dispersed. The obtained dispersed mixture is reacted with an aqueous urea solution and centrifuged. The obtained solid is washed with deionized water and ethanol and dried to obtain hydroxyapatite powder.

[0055] According to the present invention, in the synthesis of the above-mentioned hydroxyapatite, preferably, the weight ratio of the usage of NH4H2PO4, Ca(NO3)2, deionized water and urea aqueous solution is 3.45:2.1-2.8:80-87:20.

[0056] According to the present invention, in the synthesis of the above hydroxyapatite, preferably, the concentration of the urea aqueous solution is 0.007-0.009 mol / ml.

[0057] According to the present invention, in the synthesis of the above hydroxyapatite, preferably, the reaction conditions include: temperature of 110-125°C, time of 2-5h; more preferably, the reaction conditions include: temperature of 120°C, time of 3-4h.

[0058] According to the present invention, in the synthesis of the above hydroxyapatite, preferably, the washing can use one or more of deionized water, ethanol, ethyl acetate and petroleum ether; more preferably, deionized water and ethanol are used.

[0059] Examples of the organic solvent include dimethylformamide.

[0060] According to the present invention, the contacting further comprises the steps of mixing the hydroxyapatite, benzimidazole, zinc nitrate and an organic solvent, and then centrifuging, washing and drying; preferably, the contacting further comprises the steps of mixing the hydroxyapatite with a mixture of benzimidazole, zinc nitrate and an organic solvent, and then centrifuging, washing and drying.

[0061] The above-mentioned mixing conditions include: a stirring speed of 1200-2000 rpm and a time of 0.5-3 h; more preferably, the above-mentioned mixing conditions include: a stirring speed of 1500-1800 rpm and a time of 1-2 h.

[0062] The above-mentioned centrifugal separation conditions include: a rotation speed of 4000-8000 rpm, a temperature of 50-70°C, and a time of 2-6h; more preferably, the above-mentioned centrifugal separation conditions include: a rotation speed of 5000-7000 rpm, a temperature of 55-65°C, and a time of 3-5h.

[0063] The above washing can be carried out using ethyl acetate solvent.

[0064] The drying conditions include: a temperature of 60-90° C. and a time of 1-3 h; more preferably, the drying conditions include: a temperature of 70-80° C. and a time of 2-2.5 h.

[0065] According to the present invention, the dosage of the benzimidazole and zinc nitrate is selected according to the dosage of the hydroxyapatite. Preferably, the mass ratio of the hydroxyapatite, benzimidazole and zinc nitrate is 1:16-17:5-6; more preferably, the mass ratio of the hydroxyapatite, benzimidazole and zinc nitrate is 1:16.42-16.48:5.82-5.96.

[0066] According to the present invention, the amount of the organic solvent is selected according to the amount of the hydroxyapatite. Preferably, the mass ratio of the hydroxyapatite to the organic solvent is 1:80-120; more preferably, the mass ratio of the hydroxyapatite to the organic solvent is 1:90-110.

[0067] According to the present invention, in order to improve the physical properties and corrosion resistance of the composite anti-seepage coating, epoxy resin and curing agent are added in step 2).

[0068] Preferably, the epoxy resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin.

[0069] Preferably, the curing agent is selected from one or more of diethylenetriamine, triethylenetetramine and hydroxyethylethylenediamine.

[0070] According to the present invention, preferably, the mass ratio of the solid product, the epoxy resin and the curing agent is 1:11-16:3-9; more preferably, the mass ratio of the solid product, the epoxy resin and the curing agent is 1:12-15.6:3.6-7.

[0071] According to the present invention, in order to remove bubbles in the composite anti-seepage coating, the method further comprises the step of vacuum degassing the mixed product after the mixing.

[0072] Preferably, the vacuum degassing conditions include: vacuum pressure of -0.03 to -0.08 MPa, temperature of 25-35°C; more preferably, the vacuum degassing conditions include: vacuum pressure of -0.05 MPa, temperature of 28°C.

[0073] According to a second aspect of the present invention, there is provided a composite anti-seepage coating prepared by the method for preparing the composite anti-seepage coating according to the first aspect of the present invention.

[0074] According to the third aspect of the present invention, a composite anti-seepage coating is provided, wherein the composite anti-seepage coating is prepared using the composite anti-seepage coating prepared by the preparation method of the composite anti-seepage coating described in the first aspect of the present invention or the composite anti-seepage coating described in the second aspect of the present invention.

[0075] According to the present invention, preferably, the composite anti-seepage coating is obtained by coating the composite anti-seepage coating on the surface of a substrate and then curing the composite anti-seepage coating.

[0076] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.

[0077] Preparation Example 1

[0078] 2 parts by weight of 4-bromo-1,8-naphthalene anhydride (purchased from Anshan Huifeng Chemical Co., Ltd.) and 0.5 parts by weight of p-phenylenediamine (purchased from Anshan Huifeng Chemical Co., Ltd.) were dissolved in a mixed solvent of 140 parts by weight of ethanol and 10 parts by weight of water, and refluxed for 2 hours under nitrogen protection. After standing until solids precipitated, the mixture was filtered, rinsed with ethanol, and dried to obtain N-(4-aminophenyl)-4-bromo-1,8-naphthaleneimide solid.

[0079] The obtained 2.1 parts by weight of N-(4-aminophenyl)-4-bromo-1,8-naphthalimide solid and 4.2 parts by weight of piperidine (purchased from Shanghai Aladdin Chemical Co., Ltd.) were dissolved in 60 parts by weight of ethylene glycol monomethyl ether (purchased from Wuxi Meizan Chemical Co., Ltd.), refluxed for 4 hours under nitrogen protection, and then filtered and rinsed with ethanol to obtain N-(4-aminophenyl)-4-(1-piperidinyl)-1,8-naphthalimide solid.

[0080] 1.2 parts by weight of the obtained N-(4-aminophenyl)-4-(1-piperidinyl)-1,8-naphthalimide solid was dissolved in 150 parts by weight of ethanol and 20 parts by weight of acetic acid, and ethylene oxide was introduced into the obtained reaction solution under a -10°C cold bath for reaction, and the solvent was distilled off under reduced pressure to obtain a solid powder. The obtained solid powder was dissolved in dichloromethane (purchased from Wuxi Meizan Chemical Co., Ltd.), washed with a potassium carbonate aqueous solution, and then the solvent was distilled off to obtain N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide solid (NHAN).

[0081] Example 1

[0082] (1) 3.45 parts by weight of NH4H2PO4 (purchased from Sinopharm Chemical Reagent Co., Ltd.) and 2.4 parts by weight of Ca(NO3)2 (purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to 80 parts by weight of deionized water to dissolve and then ultrasonically dispersed. The resulting dispersed mixture was added to 20 parts by weight of a 0.0075 mol / mL urea aqueous solution (purchased from Shanghai Aladdin Chemical Co., Ltd.), reacted at 120° C. for 3 hours, and then centrifuged. The resulting solid was washed with deionized water and ethanol, and dried to obtain hydroxyapatite powder.

[0083] (2) 0.5 parts by weight of the hydroxyapatite powder solid was added to 50 parts by weight of a dimethylformamide solution containing 8.23 ​​parts by weight of benzimidazole and 2.91 parts by weight of zinc nitrate (both purchased from Shanghai Aladdin Chemical Co., Ltd.) in a stirring state, and the stirring was maintained for 2 hours (stirring speed was 1500 rpm), and centrifugal separation was performed (speed was 6000 rpm, temperature was 55° C., and time was 3.5 hours) to obtain a solid powder. The obtained solid powder was washed with ethyl acetate and dried (drying temperature was 75° C., time was 2 hours) to obtain modified hydroxyapatite.

[0084] (3) 0.5 parts by weight of N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide and 10 parts by weight of modified hydroxyapatite solid were stirred and mixed in 50 parts by weight of ethanol for 10 hours (mixing pressure of 10.1 MPa, temperature of 25°C), and centrifugally dried (centrifugal speed of 5000 rpm, temperature of 60°C, time of 3 hours) to obtain modified hydroxyapatite solid containing N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide. 5 parts by weight of modified hydroxyapatite solid were mixed with 70 parts by weight of bisphenol A epoxy resin (purchased from the Institute of Marine Chemistry) and stirred, and 25 parts by weight of triethylenetetramine curing agent (purchased from Aladdin Reagent) was added during the stirring process. The obtained mixture was subjected to vacuum degassing treatment (vacuum pressure -0.05 MPa, temperature 28°C) to obtain a composite anti-seepage coating S1.

[0085] Example 2

[0086] (1) 3.45 parts by weight of NH4H2PO4 (purchased from Sinopharm Chemical Reagent Co., Ltd.) and 2.2 parts by weight of Ca(NO3)2 (purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to 85 parts by weight of deionized water to dissolve and then ultrasonically dispersed. The resulting dispersed mixture was added to 20 parts by weight of a 0.008 mol / mL urea aqueous solution (purchased from Shanghai Aladdin Chemical Co., Ltd.), reacted at 120° C. for 4 hours, and then centrifuged. The resulting solid was washed with deionized water and ethanol, and dried to obtain hydroxyapatite powder.

[0087] (2) 0.5 parts by weight of the hydroxyapatite powder solid was added to 48 parts by weight of a dimethylformamide solution containing 8.24 parts by weight of benzimidazole and 2.98 parts by weight of zinc nitrate (both purchased from Sinopharm Chemical Reagent Co., Ltd.) in a stirring state, and the stirring was maintained for 1.5 hours (stirring speed was 1600 rpm), and centrifugal separation was performed (speed was 7000 rpm, temperature was 60° C., and time was 3 hours) to obtain a solid powder. The obtained solid powder was washed with ethyl acetate and dried to obtain modified hydroxyapatite.

[0088] (3) 0.5 parts by weight of N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide and 12 parts by weight of modified hydroxyapatite solid were stirred and mixed in 50 parts by weight of ethanol for 9 hours (mixing pressure of 10.5 MPa and temperature of 25°C), and centrifugal dried (centrifugal speed of 6500 rpm, temperature of 60°C, time of 5 h) to obtain modified hydroxyapatite solid containing N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide. 5 parts by weight of modified hydroxyapatite solid and 65 parts by weight of bisphenol F epoxy resin (purchased from Taiwan Nan Ya) were mixed and stirred, and 30 parts by weight of diethylenetriamine curing agent (Jinan Chuangshi Chemical) were added during the stirring process. The obtained mixture was vacuum degassed (vacuum pressure -0.05MPa, temperature 28°C) to obtain a composite anti-seepage coating S2.

[0089] Example 3

[0090] (1) 3.45 parts by weight of NH4H2PO4 (purchased from Sinopharm Chemical Reagent Co., Ltd.) and 2.7 parts by weight of Ca(NO3)2 (purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to 86 parts by weight of deionized water to dissolve and then ultrasonically dispersed. The resulting dispersed mixture was added to 20 parts by weight of a 0.0085 mol / mL urea aqueous solution (purchased from Shanghai Aladdin Chemical Co., Ltd.), fully reacted at 125° C. for 3 hours, and then centrifuged. The resulting solid was washed with deionized water and ethanol, and dried to obtain hydroxyapatite powder.

[0091] (2) 0.5 parts by weight of the hydroxyapatite powder solid was added to a stirred solution containing 8.23 ​​parts by weight of benzimidazole and 2.95 parts by weight of zinc nitrate (both purchased from Shanghai Aladdin Chemical Co., Ltd.) and 52 parts by weight of dimethylformamide, and the mixture was stirred for 2 hours (stirring speed was 1700 rpm), and centrifuged (speed was 7000 rpm, temperature was 65° C., and time was 3 minutes) to obtain a solid powder. The obtained solid powder was washed with dimethylformamide and dried to obtain modified hydroxyapatite.

[0092] (3) 0.5 parts by weight of N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide and 11 parts by weight of modified hydroxyapatite solid were stirred and mixed in 50 parts by weight of ethanol for 11 hours (mixing pressure of 10.2 MPa, temperature of 26°C), and centrifugally dried (centrifugal speed of 7000 rpm, temperature of 60°C, time of 4 hours) to obtain modified hydroxyapatite solid containing N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide. 5 parts by weight of modified hydroxyapatite solid were mixed with 70 parts by weight of phenolic epoxy resin (purchased from Shandong Lehua Chemical) and stirred, and 25 parts by weight of triethylenetetramine curing agent (purchased from Aladdin Reagent) was added during the stirring process. The obtained mixture was subjected to vacuum degassing treatment (vacuum pressure -0.05 MPa, temperature 28°C) to obtain a composite anti-seepage coating S3.

[0093] Example 4

[0094] The method of Example 1 is followed, except that in step (3) of preparing the modified hydroxyapatite solid containing N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthaleneimide, the modified hydroxyapatite is 5 parts by weight, and the composite anti-seepage coating S4 is obtained in the same manner.

[0095] Example 5

[0096] The method of Example 1 is followed, except that in step (3) of preparing a modified hydroxyapatite solid containing N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthaleneimide, the modified hydroxyapatite is 15 parts by weight, and the composite anti-seepage coating S5 is obtained in the same manner.

[0097] Example 6

[0098] The method of Example 1 is followed, except that the fluorescent probe molecule N-[4-di(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthaleneimide is replaced with the same amount of N-(2-thiazolyl)-4-(1-piperidinyl)-1,8-naphthaleneimide to obtain the composite anti-seepage coating S6 in the same manner.

[0099] Example 7

[0100] The method of Example 1 was followed, except that the fluorescent probe molecule N-[4-di(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthaleneimide was replaced with the same amount of N-(2-pyridinyl)-4-(1-piperidinyl)-1,8-naphthaleneimide to obtain the composite anti-seepage coating S7 in the same manner.

[0101] Comparative Example 1

[0102] The method of Example 1 was followed, except that unmodified hydroxyapatite was used.

[0103] 0.5 parts by weight of N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide and 10 parts by weight of hydroxyapatite solid were stirred and mixed in 50 parts by weight of ethanol for 10 hours (mixing pressure of 10.1MPa, temperature of 25°C), and centrifugal drying (centrifugal speed of 5000 rpm, temperature of 60°C, time of 3h) was performed to obtain hydroxyapatite solid containing N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalimide. 5 parts by weight of hydroxyapatite solid were mixed with 70 parts by weight of bisphenol A epoxy resin (purchased from the Institute of Marine Chemistry) and stirred, and 25 parts by weight of triethylenetetramine curing agent (purchased from Aladdin Reagent) were added during the stirring process. The obtained mixture was vacuum degassed (vacuum pressure -0.05MPa, temperature 28°C) to obtain a composite anti-seepage coating D1.

[0104] Comparative Example 2

[0105] The method of Example 1 is followed, except that in step (3) of preparing a modified hydroxyapatite solid containing N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthaleneimide, the modified hydroxyapatite is 2 parts by weight, and the composite anti-seepage coating D2 is obtained in the same manner.

[0106] Comparative Example 3

[0107] The method of Example 1 was followed, except that in step (3) of preparing a modified hydroxyapatite solid containing N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthaleneimide, the modified hydroxyapatite was 20 parts by weight, and the composite anti-seepage coating D3 was obtained in the same manner.

[0108] Comparative Example 4

[0109] 1.0g aniline trimer and 1.0g graphene (purchased from Ningbo Moxi Technology Co., Ltd.) are dispersed in 1.0L toluene solution, and ultrasonic dispersion is performed for 1 hour to obtain a graphene dispersion. The content of graphene in toluene after modification by aniline trimer reaches 1g / L. The graphene dispersion is added to 45g epoxy resin (model E44, purchased from Jiangsu Wujiang Heli Resin Factory), and a mixture A is obtained after mixing. 2g leveling agent, 4g defoamer, 2g anti-settling agent and 45g polyamide curing agent are added successively to the mixture A, and stirred evenly to obtain a composite anti-seepage coating D4.

[0110] Comparative Example 5

[0111] Take 3g of copper nitrate and disperse it in 100mL of deionized water, pour it into a round-bottom flask after uniform dissolution, take 0.2g of terephthalic acid and disperse it in 100mL of deionized water, pour it into the above round-bottom flask after uniform dissolution to obtain a mixed solution, add 1mL of 1M sodium hydroxide solution to the above mixed solution, place the round-bottom flask containing the mixed solution in an oil bath, and the mechanical stirring rate is 800r / min. The temperature of the oil bath is set to 50°C. After stirring for 5h, the reaction suspension is centrifuged at a speed of 5000r / min for 5min, and the solid obtained by centrifugation is placed in a 50°C oven and dried for 30h to obtain a copper ion organic framework nanomaterial. The organic framework nanomaterial with a mass fraction of 2wt% is added to the polyurethane resin and mixed evenly, and then placed in a vacuum oven with a vacuum degree of -0.05MPa for 20min to obtain a resin mixture. The resin mixture was coated on the carbon steel surface, cured at room temperature for 5 hours, and then cured in a 60°C oven for 15 hours to obtain a corrosion self-diagnostic coating based on ion exchange. The thickness of the coating after curing was 40 μm, and a composite anti-seepage coating D5 was obtained.

[0112] Comparative Example 6

[0113] Precursor solution synthesis: polymer 1, polymer 2, solvent 1, solvent 2, and copper nitrate were weighed in a mass ratio of 0.5:0.5:5:5:1. 0.5g polyvinyl butyral and 0.5g polyvinyl pyrrolidone were added to a mixed solution of 5mL ethanol and 5mL N,N-dimethylformamide, and stirred at 400rmp for 24 hours at a temperature of 25°C. Then 1g copper nitrate was added and stirred at 400rmp for 10 hours at a temperature of 25°C. Electrospinning synthesis. The tin foil was fixed on the drum receiver according to the appropriate size, the syringe of the precursor solution was installed, and then the power was turned on for electrospinning. The translation distance was set to 60mm, the front dead point of the push device was set to zero, the syringe capacity was 5mL, the positive voltage was set to 25KV, the negative voltage was set to 4KV, the push rate was 0.08mm / min, the receiving rate was 100 turns / min, the translation speed was 40mm / min, and the receiving distance was 20cm. After spinning for 3 hours, nanofiber filler PVB / PVP-Cu2(OH)3NO3 was obtained. The obtained nanofiber filler was mixed with mixed epoxy resin in a thickness ratio of 1:5, coated on the surface of the metal substrate, and dried at room temperature for 72 hours to obtain a composite anti-seepage coating D6.

[0114] Test Example 1

[0115] The obtained intelligent anti-seepage coatings S1-S7 and coatings D1-D6 were drop-coated on Q235 steel plates, and the coatings were applied on Q235 steel plates with a rod coater to a thickness of 100 microns after curing. After curing at room temperature for 10 hours and at 60°C for 5 hours, the water seepage resistance time of the coatings formed by the coatings was tested using the test method described in GB / T16777-2008. The results are shown in Table 1.

[0116] Table 1

[0117] Water seepage resistance time / h S1 1800 S2 1800 S3 1750 S4 1400 S5 1430 S6 1600 S7 1580 D1 1020 D2 1020 D3 1050 D4 700 D5 600 D6 1100

[0118] Test Example 2

[0119] The obtained intelligent anti-seepage coatings S1-S7 and coatings D1-D6 were drop-coated on Q235 steel plates, and the coatings were applied on Q235 steel plates with a rod coater with a requirement of a coating thickness of 100 μm after curing. After curing at room temperature for 10 hours and at 60°C for 5 hours, the test method described in GB / T16777-2008 was used, with the difference that the test medium water was replaced with simulated ethanol gasoline (the composition ratio refers to EU standard EN13160-7-2003), and the oil leakage resistance time of the coating formed by the coating was tested. The results are shown in Table 2.

[0120] Table 2

[0121] Oil resistant leakage time / h S1 1300 S2 1200 S3 1250 S4 950 S5 930 S6 1100 S7 1080 D1 550 D2 600 D3 630 D4 550 D5 400 D6 350

[0122] Test Example 3

[0123] The obtained intelligent anti-seepage coatings S1-S7 and coatings D1-D6 were dripped on the copper foil, and the coatings were coated on the copper foil with a rod coater so that the coating thickness after curing was 50 μm. After curing at room temperature for 10 hours and at 60°C for 5 hours, the samples were used as samples for corrosion resistance test using the method for determination of neutral salt spray resistance of paints and varnishes in GB / T1771-2007. The results are shown in Table 3.

[0124] Table 3

[0125] Salt spray corrosion resistance time / h S1 4200 S2 4500 S3 4300 S4 4000 S5 3900 S6 4100 S7 4000 D1 2000 D2 2900 D3 3000 D4 2800 D5 1400 D6 1800

[0126] Test Example 4

[0127] The obtained intelligent anti-seepage coatings S1-S7 and coatings D1-D6 were dripped onto 13 identical Q235 steel plates, and the coatings were applied to the Q235 steel plates with a rod coating machine with a thickness of 5 μm after curing. After curing at room temperature for 10 hours and at 60°C for 5 hours, the 13 coated steel plates were placed in 13 identical beakers containing 3.5wt% NaCl solution. After soaking for 6 hours, it was found that the steel plates coated with D1-D6 coatings had no obvious changes, while the surface of the steel plates coated with S1-S7 coatings had obvious fluorescence reactions under dark conditions, and the fluorescence intensity became stronger as the degree of corrosion deepened. After soaking for another 6 hours, the fluorescence intensity of the corroded area on the surface of the steel plates coated with S1-S7 coatings continued to increase, and red marks appeared on the surface of the steel plates coated with D5 coatings. This shows that the anti-seepage coatings S1-S7 prepared according to the method described in the present invention have a self-diagnosis function for metal corrosion, and compared with the D5 coating, the sensitivity of corrosion self-diagnosis is higher. In addition, compared with the anti-seepage coating containing hydroxyapatite grafted with a molecular sieve imidazole skeleton described in the present invention, the anti-seepage coating D1 containing pure hydroxyapatite is more likely to release fluorescent molecular probes prematurely during the service process of the coating, causing it to lose its activity and fail to achieve the corrosion self-diagnosis effect.

[0128] Test Example 5

[0129] The obtained intelligent anti-seepage coatings S1-S7 and coatings D1-D6 were drop-coated on Q235 steel plates, and the coatings were applied to the Q235 steel plates with a rod coater to a thickness of 100 μm after curing. After curing at room temperature for 10 hours and at 60°C for 5 hours, the water seepage resistance time of the coatings formed by the coatings was tested using the test method described in GB / T16777-2008, and 100 hours after the start of the test, the same scratches with a width of 50 μm and a length of 1 cm were made on the coating surfaces of 13 steel plates using a scalpel, and the water seepage resistance time of the coatings formed by the coatings was continued to be tested under the test conditions of GB / T16777-2008. The results are shown in Table 4.

[0130] Table 4

[0131] Water seepage resistance time / h S1 1600 S2 1550 S3 1600 S4 1240 S5 1200 S6 1400 S7 1420 D1 520 D2 850 D3 790 D4 300 D5 420 D6 840

[0132] By comparing the experimental results of test examples 1 to 5, it can be seen that the intelligent anti-seepage coating prepared by the method of the present invention has better resistance to corrosive media such as salt spray, water, ethanol gasoline, etc. compared with the prior art, and also shows higher corrosion self-diagnosis sensitivity and scratch damage healing efficiency. In addition, the molecular sieve imidazole skeleton on the surface of hydroxyapatite is the key to the self-healing function of the anti-seepage material.

[0133] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a composite anti-seepage coating, characterized in that: The Method The following steps are included: 1) In the presence of a solvent, mixing the fluorescent probe molecule and the modified hydroxyapatite, and drying them to obtain a solid product containing the fluorescent molecular probe; 2) mixing the solid product in step 1) with an epoxy resin and a curing agent to obtain a composite anti-seepage coating; The mass ratio of the fluorescent probe molecule to the modified hydroxyapatite is 1:5-35. The modified hydroxyapatite is hydroxyapatite grafted with molecular sieve imidazole framework material.

2. The method according to claim 1, wherein: In step 1), the mass ratio of the fluorescent probe molecule to the modified hydroxyapatite is 1:15-25.

3. The method according to claim 1, wherein: In step 1), the weight ratio of the modified hydroxyapatite to the solvent is 1:80-120.

4. The method according to claim 1, wherein: In step 1), the solvent is one or more of ethanol, ether and phenol, preferably ethanol.

5. The method according to claim 1, wherein: In step 1), the fluorescent probe molecule is one or more of N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalene imide, N-(2-thiazolyl)-4-(1-piperidinyl)-1,8-naphthalene imide and N-(2-pyridinyl)-4-(1-piperidinyl)-1,8-naphthalene imide, preferably N-[4-bis(2-hydroxyethyl)aminophenyl]-4-(1-piperidinyl)-1,8-naphthalene imide.

6. The method according to claim 1, wherein: In step 1), the mixing conditions include: temperature of 20-30°C, time of 8-12h, and pressure of 8-12MPa; Preferably, the mixing conditions of step 1) include: temperature of 24-26° C., time of 9-11 h, and pressure of 10-11 MPa.

7. The method according to claim 1, wherein: In step 1), the drying is centrifugal drying, and the drying conditions include: a centrifugal speed of 4000-8000 rpm, a temperature of 50-70° C., and a time of 2-6 h; Preferably, the drying conditions include: a centrifugal speed of 5000-7000 rpm, a temperature of 55-65° C., and a drying time of 3-5 h.

8. The method according to claim 1, wherein: The molecular sieve imidazole framework material is a metal organic framework material, preferably a metal organic framework material ZIF-7.

9. The method according to claim 1, wherein: The modified hydroxyapatite is obtained by contacting hydroxyapatite with benzimidazole and zinc nitrate in the presence of an organic solvent.

10. The method according to claim 9, wherein: The mass ratio of hydroxyapatite, benzimidazole and zinc nitrate is 1:16-17:5-6; Preferably, the mass ratio of the hydroxyapatite to the organic solvent is 1:80-120.

11. The method according to claim 9, wherein: The organic solvent is dimethylformamide.

12. The method according to claim 1, wherein: In step 2), the mass ratio of the solid product, the epoxy resin and the curing agent is 1:11-16:3-9; Preferably, the mass ratio of the solid product, the epoxy resin and the curing agent is 1:12-15.6:3.6-7.

13. The method according to claim 1, wherein: In step 2), the epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin; Preferably, the curing agent is one or more of diethylenetriamine, triethylenetetramine and hydroxyethylethylenediamine.

14. The method according to claim 1, wherein: The method further comprises the step of vacuum degassing the mixed product after the mixing; The vacuum degassing conditions include: vacuum pressure of -0.03 to -0.08 MPa and temperature of 25-35°C.

15. The composite anti-seepage coating prepared by the preparation method of the composite anti-seepage coating according to any one of claims 1 to 14.

16. A composite anti-seepage coating, characterized in that: The composite anti-seepage coating is prepared by using the composite anti-seepage coating prepared by the preparation method of the composite anti-seepage coating described in any one of claims 1 to 14 or the composite anti-seepage coating described in claim 15.

17. The composite anti-seepage coating according to claim 16, wherein: The composite anti-seepage coating is obtained by coating the composite anti-seepage coating on the surface of a substrate and then curing the coating.

Citation Information

Patent Citations

  • Graphene composite coating, graphene composite paint and preparation method thereof

    CN105802452A

  • Coating

    CN108822606A

  • Fluorescent self-warning and corrosion-inhibition self-repairing nano anticorrosive coating and preparation method thereof

    CN114634746A

  • Preparation method of self-repairing anti-corrosion coating based on ZIFs

    CN116004086A

  • Application of pH-responsive fluorescent MOFs composite material to intelligent anticorrosive coating material

    CN116376402A